Analisa Pemeliharaan Jalan Berkala Kota Jambi dengan Metode Sdi (Surface Distress Index) - Purba, Suman Jaya Dinata; Yamali, Fakhrul Rozi; Dony, Wari (Jurnal Civronlit Unbari, 2024)
Roads are land transportation infrastructure which includes all parts of the road. Good road conditions really support the smooth running of the economy in an area so that road maintenance is very important so that the smooth running of the economy is not disrupted by poor road infrastructure. The form of road maintenance depends on the results of the assessment of the condition of the damage. The road surface has been determined visually, the method used is the Surface Distress Index (SDI) method. According to Suswandi (2008), assessing the level of road damage is an important aspect in determining road maintenance and repair activities. Small damage that is not immediately anticipated causes the damage to become more severe, the impact becomes wider and reduces the capacity of the road itself. Therefore, researchers want to technically review the condition of the surface pavement of Jalan Swadaya Raya in Alam Barajo District using this method visually, with a length of 800 m and a width of 4 m experiencing damage in several segments which is quite disturbing the smooth running of the road.